The Improving Syntax Learning Achievement using Lesson Study Based Learning Management: A Classroom Action Research - Moh Tosin; Sulistyaningsih Sulistyaningsih; Lailatul Musyarofah (ITScience (Information Technology and Science), 2023)
Classroom Action research is motivated by the low value of English, especially when it comes to syntax learning, and students are not brave, fearful or confident in syntax English. The aim of this research was to learn about the process of lesson study based learning management and to increase syntax learning achievement using lesson study based learning management on four semesters at STKIP PGRI Sidoarjo. The descriptive qualitative and classroom action research methods were used in this research. This research was conducted from April to June 2022, located in STKIP PGRI Sidoarjo on four semester of English Education. This research was designed as a classroom action research project with lesson study-based learning management. Two cycles were used to implement the improvements. The lesson study observation sheet and the students' activity observation sheet were used as research instruments during the learning process. The results of the process of lesson study based learning management revealed that it was a cyclical process involving the development of lesson plans, the implementation of learning (do, open class), and the evaluation of learning (see), and that there was an improvement in terms of syntax learning achievement through lesson study based learning management on four semesters at STKIP PGRI Sidoarjo when lesson study based learning management was implemented